Response to the Round Table on Why Did We Choose to Industrialize? Montreal 1819–1849 - SWEENY, ROBERT (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2017)
Author Robert C.H. Sweeny responds to comments on his award-winning book, Why Did We Choose to Industrialize? Montreal 1819–1849.